Design of compact and high gain dual-band four-port MIMO antenna array for mm-wave 5G Communications - Mohammed Mahaboob Basha; Pendli Pradeep; Srinivasulu Gundala; Javed Syed (Results in Engineering)
This article presents a dual-band compact dual-port and quad-port Multiple-Input Multiple-Output (MIMO) array antenna that uses an array antenna of two elements with high isolation, exclusively designed for 5 G applications in the millimeter-wave band. A Corporate Feed network is employed to excite the two-element array antennas. The antenna design comprises a simple strip at the edge of the patch with a circular slot on the ground plane. These components improve an impedance matching, bandwidth, and radiation intensity characteristics. Ansys HFSS, a 3D electromagnetic (EM) simulation software, is utilized for the design process. The proposed innovative dual-band quad-port MIMO antenna systems are characterized on a Rogers RT/duroid 5880 (tm) substrate with a dielectric constant 2.2 and a thickness of 0.79 mm, operating at frequencies of 28/38 GHz. The dual-band frequencies span from 27.1 GHz to 28.71 GHz and 36.2 GHz to 42 GHz, with isolation levels observed below -27 dB and -20 dB in dual-bands, respectively. Remarkably, the proposed 4-port MIMO antennas achieved remarkable maximum gain of 10.4 dBi, at the first band at 28 GHz, and 10.1 dBi at the second band at 38 GHz. The suggested antennas exhibit directional and semi-omni directional radiation patterns in the lower and upper-frequency bands. To validate the performance, the MIMO structure is fabricated and measured. The simulated and measured results are in good coherence. Moreover, the MIMO antenna diversity parameters are characterized to remain below the standard limits. The proposed dual-port and quad-port MIMO array antennas can be used for 5 G mm wave applications at dual-band and hold significant promise.